Miller, Chris; La guerra de los chips - Viladomiu, Lourdes (Revista de Economía Crítica, 2024)
Reseña del libro de Miller, Chris; La guerra de los chips, Ed. Península, 2023, (pp. 544), ISBN 978-84-1100-198-4